2022
DOI: 10.3390/life12030444
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Respiratory Compensation Point by Detecting Changes in Intercostal Muscles Oxygenation by Using Near-Infrared Spectroscopy

Abstract: This study aimed to evaluate if the changes in oxygen saturation levels at intercostal muscles (SmO2-m.intercostales) assessed by near-infrared spectroscopy (NIRS) using a wearable device could determine the respiratory compensation point (RCP) during exercise. Fifteen healthy competitive triathletes (eight males; 29 ± 6 years; height 167.6 ± 25.6 cm; weight 69.2 ± 9.4 kg; V˙O2-máx 58.4 ± 8.1 mL·kg−1·min−1) were evaluated in a cycle ergometer during the maximal oxygen-uptake test (V˙O2-máx), while lung ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…The wearable lactate threshold sensor could be implemented by coaches and athletes Cayot et al 46 N = 9 (M); 5 (F) Recreationally 2 × GXT (separated by 7–10 days) 5-min W-UP (25 W) ↑ 25 W every 180 s * Cycle ergometer LT 2 Moxy VL MOT 2 detection was moderately correlated with the LT 2 and the heart rate. The results do not support the use of two different mathematical methods for MOT 2 determination Contreras-Briceño et al 39 N = 8 (M); 7 (F) Highly trained triathletes GXT 2-min rest 3-min W-UP (100 W) ↑ 20 W every 80 s * Bike on a cycle ergometer VT 2 Moxy 7th IC A good-to-excellent correlation was obtained between MOT 2 and VT 2 for each variable of all analyses in the 7th IC, muscle Driller et al 47 N = 10 (M); 5 (F) Highly Trained Cyclists GXT 3-min 80–120 W ↑ 20 W every 180 s * Bicycle on an ergometer LT 2 BSX Insight GC LT 2 determination through MOT 2 showed an excellent correlation during cycling. These results were shown in all methods for LT 2 detection Farzam et al 48 N = 15 (M); 3 (F) Recreationally GXT 4-min 30 W ↑30 W every 240 s * Cycle ergometer LT 2 Humon Hex, MetaOX* RF MOT 2 determination showed good agreements with LT 2 NIRS portable and NIRS non-portable showed a good correlation during the exercise.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The wearable lactate threshold sensor could be implemented by coaches and athletes Cayot et al 46 N = 9 (M); 5 (F) Recreationally 2 × GXT (separated by 7–10 days) 5-min W-UP (25 W) ↑ 25 W every 180 s * Cycle ergometer LT 2 Moxy VL MOT 2 detection was moderately correlated with the LT 2 and the heart rate. The results do not support the use of two different mathematical methods for MOT 2 determination Contreras-Briceño et al 39 N = 8 (M); 7 (F) Highly trained triathletes GXT 2-min rest 3-min W-UP (100 W) ↑ 20 W every 80 s * Bike on a cycle ergometer VT 2 Moxy 7th IC A good-to-excellent correlation was obtained between MOT 2 and VT 2 for each variable of all analyses in the 7th IC, muscle Driller et al 47 N = 10 (M); 5 (F) Highly Trained Cyclists GXT 3-min 80–120 W ↑ 20 W every 180 s * Bicycle on an ergometer LT 2 BSX Insight GC LT 2 determination through MOT 2 showed an excellent correlation during cycling. These results were shown in all methods for LT 2 detection Farzam et al 48 N = 15 (M); 3 (F) Recreationally GXT 4-min 30 W ↑30 W every 240 s * Cycle ergometer LT 2 Humon Hex, MetaOX* RF MOT 2 determination showed good agreements with LT 2 NIRS portable and NIRS non-portable showed a good correlation during the exercise.…”
Section: Resultsmentioning
confidence: 77%
“…Our meta-analyses were focused on showing whether the exercise intensity where the first and second thresholds were detected using the portable NIRS was more reliable than the gold standards methods (gas exchange and blood lactate). Table 1 shows how the relationship between MOT and VT was analyzed in 7 studies 16 , 25 , 39 43 and in 9 studies for LT 17 , 26 , 41 , 44 – 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A computation window of 2 s was used. SmO 2 changes during RMT session (ΔSMO 2 B) and SmO 2 recovery after RMT session (ΔSMO 2 A) were recorded to assess exercise intensity ( Contreras-Briceño et al, 2022 ) as below: …”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the general practice for study design has been comparing oxygen uptake data to muscle deoxygenation [ 14 , 15 , 16 ]. Although, commonly available NIRS devices measure oxygen saturation in arbitrary units and therefore it would be more applicable to use the same parameters the data are measured in as has been performed in latter studies [ 11 , 12 , 13 , 17 , 18 ]. As mentioned before, many studies have been performed to establish the correlation between thresholds identified using pulmonary gas exchange devices and NIRS signals.…”
Section: Introductionmentioning
confidence: 99%